2015
DOI: 10.4168/aair.2015.7.2.148
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Allergic Rhinitis Among Adults in Urban and Rural Areas of China: A Population-Based Cross-Sectional Survey

Abstract: PurposeThe aim of the present study was to compare the prevalence of self-reported and confirmable allergic rhinitis (AR) with positive skin prick test (SPT) results among adults living in urban and rural areas of China.MethodsAdults from a community in Beijing and a village in Baoding were selected as representative urban and rural dwellers, respectively. All eligible residents were enrolled from the population register and received a face-to-face interview using modified validated questionnaires. Equal sets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 34 publications
0
38
2
Order By: Relevance
“…We have previously reported that the positive SPT rate among subjects with self-reported AR was 32.5% in Baoding, in central China; with Cwa climate 29 . In the present study, we estimated that to screen >96% sensitized patients, with a 4% margin of error and a 2-tailed α value of 0.05, the size of the cohort in central China needed to be 4987.…”
Section: Methodsmentioning
confidence: 94%
“…We have previously reported that the positive SPT rate among subjects with self-reported AR was 32.5% in Baoding, in central China; with Cwa climate 29 . In the present study, we estimated that to screen >96% sensitized patients, with a 4% margin of error and a 2-tailed α value of 0.05, the size of the cohort in central China needed to be 4987.…”
Section: Methodsmentioning
confidence: 94%
“…These questionnaires were adapted from the well-documented and validated questionnaires used in the International Study of Asthma and Allergies in Childhood and the European Community Respiratory Health Survey studies, as we have described previously. 20 Furthermore, the criteria used to diagnose AR were consistent with those of the ARIA (Allergic Rhinitis and Its Impact on Asthma) guidelines, 10 and included a history of the typical symptoms of rhinorrhea, nasal congestion, sneezing, and/ or nasal itching during the past 12 months concomitantly with positive SPT to at least one aeroallergen. NAR was diagnosed similarly based on the history of symptoms, but with a negative SPT, whereas "no-rhinitis" was classified on the basis of the absence of any of these characteristic symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…The reported incidence of AR is 11.8–46% worldwide [1, 2] and 11.1–19.1% [3, 4] in China. Allergen avoidance is strongly recommended for AR patients.…”
Section: Introductionmentioning
confidence: 99%